Diagnostic accuracy of magnetic resonance-guided prostate biopsy and template-guided transperineal saturation biopsy. Issue 38 (September 2018) - Zhou, Yi; Zhou, Zhien; Li, Qianyue; Xu, Yinyan; Sun, Hao; Xiao, Yu; Liang, Zhiyong; Yan, Weigang; Ji, Zhigang; Li, Hanzhong
Abstract : Abstract: To compare the accuracy of magnetic resonance-guided prostate biopsy (MR-GPB) and template-guided transperineal prostate saturation biopsy (TTPSB). A total of 219 patients with elevated prostate-specific antigen, abnormal digital rectal examination or ultrasound findings were enrolled. All patients underwent multiparametric magnetic resonance image (mpMRI). Patients with a Prostate Imaging Reporting and Data System (PI-RADS) score of 3 to 5 underwent MR-GPB using 2 to 5 biopsy cores and then immediately underwent an 11-region TTPSB. Patients with a PI-RADS score of 1 to 2 underwent TTPSB alone. We compared the detection rates for any cancer, clinically significant prostate cancer (csPCA), and the spatial distribution of missed csPCA lesions. Among the 219 cases, 66 (30.1%) had a PI-RADS score of 1 to 2 on mpMRI. The detection rate of TTPSB in these patients was 9.1% (6/66). In total, detection rates for any cancer and csPCA were 48.9% (107/219) and 42.9% (94/219), respectively. Detection rates for any cancer (TTPSB 87/219, 39.7%; MR-GPB76/219, 34.7%, P = .161) and csPCA (TTPSB 76/219, 34.7%; MR-GPB 72/219, 32.9%, P = .636) did not significantly differ between the 2 groups. The csPCA lesions missed by MR-GPB were most commonly located on the left (8.5%, 8/94) and right (9.6%, 9/94) sides of the urethra. MR-GPB can reduce the rate of unnecessary prostate biopsies by approximately 30% and exhibits an efficacy comparable to TTPSB for the detection of any cancer and csPCA. Nevertheless, approximately 1/4 of csPCAs were missed by MR-GPB and were most commonly located on both sides of the urethra.